Réponses

2013-03-23T21:59:43+01:00

pour la question n°1 tu auras (a-b)(a+b) donc { (1-2x-3) (1-2x+3) } une fois resolu c'est bon

2013-03-23T22:13:02+01:00

1) f(x) = 1 + 4x² - 4x - 9 = 4x² - 4x - 8


2) f(x) = (1-2x -3)(1-2x + 3) = (-2 - 2x)(4 - 2x)

 

3) f(2/3) = (1 - 4/3)² - 9 = 1/9 - 9 = -80/9
     f(1/2 + V2) = -1

 

6) tableau:
                      -oo              -1               2               +oo
4-2x                         +                 +      0        --
-2-2x                        +        0       --               --
f(x)                            +        0       --      0       +

 

solution: ]-oo ; -1]U[2 ; +oo[